2019
DOI: 10.1653/024.102.0141
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Detected Exotic Ambrosia Beetle in Argentina: Euwallacea interjectus (Coleoptera: Curculionidae: Scolytinae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…They were introduced into North America in 1970s and they are widely distributed in many US States (Cognato et al, 2015;EPPO, 2020). In 2019 Euwallacea interjectus was introduced also in Argentina (Landi et al, 2019).…”
Section: Pra Informationmentioning
confidence: 99%
“…They were introduced into North America in 1970s and they are widely distributed in many US States (Cognato et al, 2015;EPPO, 2020). In 2019 Euwallacea interjectus was introduced also in Argentina (Landi et al, 2019).…”
Section: Pra Informationmentioning
confidence: 99%
“…It was introduced into North America in 1970s and it is widely distributed in many US States -Florida, Georgia, Kentucky, Louisiana, South Carolina, Texas, Virginia and Hawaii (Cognato et al, 2015;EPPO, 2020). In 2019, E. interjectus has been introduced also in Argentina (Landi et al, 2019).…”
Section: Evaluation Of the Implementation And Relevance Of Specific M...mentioning
confidence: 99%
“…Euwallacea interjectus massively attacks water stressed poplar trees in Argentina (Landi et al, 2019), and it contributed to fig wilt as a vector of fungi Ceratocystis ficicola in Japan (Kajii et al, 2013). Kasson et al (2015) indicated that E. validus could be linked to the transmission of Verticillium nonalfalfae, which is causing severe vascular wilt disease to several plants and crops.…”
Section: Evaluation Of the Implementation And Relevance Of Specific M...mentioning
confidence: 99%
“…The ambrosia beetle, Euwallacea interjectus (Blandford) (Coleoptera: Curculionidae: Scolytinae), is a wood-boring pest found in tree species such as poplar trees in Argentina and China, and box elder trees (Acer negundo L.) in the United States [23][24][25][26]. In Japan, E. interjectus is a vector of Ceratocystis ficicola Kajitani et Masuya (Microascales: Ceratocystidaceae) [27][28][29], a pathogenic fungus that causes wilt disease in fig trees (Ficus carica L.) [28,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%